Tolerance in Persepective of Qur’an and Bibel (Comparative Analysis of Religious Tolerance in Diverses Community) - Muhammad Hifdil Islam (HUMANISTIKA : Jurnal Keislaman, 2017)
Humans are both indiviudu creatures as well as social beings. As social beings of course human beings are required to be able to interact with other individuals in order to meet their needs. In living a social life in society, an individual will be faced with groups of different colors with him one of which is the difference of religion. In living his social life can not be denied there will be friction-friction that will occur between groups of people, both related to race and religion. In order to maintain unity and unity in society it is necessary to respect each other and respect each other, so that friction-friction that can lead to disputes can be avoided. Communities are also required to keep each other’s rights and obligations between them from each other.